Experimental investigation of drying behaviour and conditions of pumpkin slices via a cyclone-type dryer - Akpinar, EK; Midilli, A; Bicer, Y (Wiley, 2003)
This paper describes an experimental investigation of the drying behaviour and conditions of pumpkin slices via a convective cyclone-type dryer. Drying experiments were conducted at air inlet temperatures of 60, 70 and 80 degreesC and air velocities of 1 and 1.5 m s(-1). Samples of 200 g of cylindrical pumpkin slices (thickness 5 mm x diameter 35 mm) were arranged in a single layer on each of two trays. The least squares method was applied to derive the drying curve equation of samples. During the experiments the following parameters were measured: weight loss, temperature, relative moisture and velocity. From these parameters, dimensionless mass loss, moisture content, mass shrinkage and drying rate of samples were calculated and are discussed in detail. Additionally, the transport of water during dehydration was described by the diffusion mechanism, and Fick's equation was used for evaluation of the experimental data. The linear sections of drying curves were analysed by linear regression to obtain the moisture diffusivities. It was found that pumpkin slices would dry perfectly within 340 - 720 min under these drying conditions. The convective cyclone dryer could also be used to dry other products. Thus it is expected that this new dryer will help farmers and producers to reduce the cost of drying. (C) 2003 Society of Chemical Industry.
Keywords: drying; single layer; dryer; pumpkin; moisture ratio; drying rate; mass shrinkage; diffusion